2022
DOI: 10.4314/tjpr.v21i5.27
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant, an estrogen receptor inhibitor, relieves postoperative hemorrhoid edema via up-regulation of miR- 424-5p

Abstract: Purpose: To investigate estrogen receptor (ER) expression in postoperative hemorrhoid edema tissues, and the likely mechanism involved in fulvestrant-mediated reduction of postoperative hemorrhoid edema.Methods: One hundred and eighty-five patients admitted to Jinshan Hospital of Fudan University, Shanghai who accepted hemorrhoidectomy were enrolled in this study. Primary cells were extracted from the anal margin tissues of patients for the determination of changes in ERα and vascular endothelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Within this range of 87 drugs, a diverse landscape emerged: ketamine (NCT04248205) was under active clinical investigation for hemorrhoids, fulvestrant was supported by preclinical in vitro models demonstrating potential efficacy for hemorrhoids ( Fanyu Meng et al, 2022 ), and methylene blue was supported by case series evidence for hemorrhoids ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ), as shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this range of 87 drugs, a diverse landscape emerged: ketamine (NCT04248205) was under active clinical investigation for hemorrhoids, fulvestrant was supported by preclinical in vitro models demonstrating potential efficacy for hemorrhoids ( Fanyu Meng et al, 2022 ), and methylene blue was supported by case series evidence for hemorrhoids ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ), as shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It offers superior analgesia compared to placebo without affecting cognitive function, hence relieving post-hemorrhoidectomy pain. Fulvestrant, an estrogen receptor antagonist, has shown promise in preclinical in vitro models by inhibiting ERα, thereby reducing VEGF expression and mitigating postoperative hemorrhoid edema ( Fanyu Meng et al, 2022 ). Methylene blue, supported by case series evidence, demonstrates anti-inflammatory effects by suppressing nitric oxide production, ultimately alleviating post-hemorrhoidectomy pain ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%